Peanut butter consumption patterns of middle and low income families in Northern Luzon - Manique, Donna Myn G.; Francisco, Ma. Leonora dL. (1999)
A study on the peanut butter consumption of low and middle income families in Northern Luzon, specifically in Laoag City and Baguio City was conducted. Majority of the respondents were 20-39 years old, predominantly female and were married. A high percentage had college and employed full-time. Nutrients, price, convenience and packaging were the most important factors to consider when buying food. Low and middle-income families had slightly different preference on the brand of peanut butter, its color, its kind (firm or flowing), its sweetness and its type (smooth and creamy or chunky). Lady's Choice was very popular among middle income families while homemade and locally produced peanut butter were popular among low income families. The firm kind, sweet and brown-colored peanut butter was preferred by both income families. Furthermore, the middle and low-income families preferred the smooth and cream type peanut butter. Most of the respondents were aware of Vitamin A and Vitamin A-fortified products. Most of them were willing to patronize a Vitamin A-fortified peanut butter. Moreover, they are willing to pay additional amount to its original price.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut butter consumption -- Philippines; Family -- Philippines